Validation of Game-Based Activities in Teaching Grade 7-Biology - Lasala Jr, N. L. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
The use of game-based activities in education has been recognized as an innovative alternative instructional material. As any sort of instructional material is essential to the teaching and learning process, it is imperative to check its quality before widespread utilization to ensure effectiveness. This study aims to evaluate the validity of the developed lessons in Ecosystem integrating game-based activities (GBAs) namely (1) THE CONQUEST, (2) ECO-DAMA, (3) ECO-CHALLENGE, and (4) ECO-WARRIOR for Grade 7 Biology. This research employed descriptive developmental research design involving 8 experts and 66 students chosen through purposive sampling. Experts used the DepEd standards for non-print resources while students were given the evaluation checklist and asked to write journals for the validation. Results show that the GBAs met all of the LRMDS DepEd's standards for non-print resources and were deemed